THE USE OF INDONESIAN SPEECH AS A SEMIOTIC SYSTEM OF THE UNIVERSITAS PENDIDIKAN INDONESIA STUDENTS - Sarmadan Sarmadan; Cecep Dudung Julianto; Bayu Dwi Nurwicaksono (Universitas Sembilanbelas November Kolaka, 2016)
This study seeked to reveal the meaning behind the speech language used by the Masters Students of Indonesian Education who were multicultural at Universitas Pendidikan Indonesia (UPI) in the study of language as a semiotic system. As stated by Lyons (1979: 74) that the language is a semiotic system (language is semiotic system) consisting of verbal language that is informative-communicative and informative nonverbal language. The results showed that the use of speech of theMasters students at Indonesian Education Study Program at UPI particularly on the class B-2011 in terms of communicationwas communicative-informative. In addition, there was a relationship between verbal and nonverbal language. The relationship between the verbal and nonverbal was mutual support between the two. Verbal supported nonverbal communication such as nodding, hand gestures, facial gaze, and others. Similarly, supported nonverbal communication in the form of verbal intonation, tone, tempos, and prosodic. The implication of this research in education is that the cultural and psychological factors affect the way people communicate in the form of verbal and nonverbal. Therefore in educational communication both factors that must be considered in order to avoid culture shock.